(untitled) (Nordic Journal of African Studies, 2008)
Any African Studies discourse that overlooks the role and place of language would be incomplete because language occupies an important position in any meaningful dialogue on African development and on Africa’s engagement with herself and with the wider international community. The premise of this article is that African Studies is about local and Diaspora African identities, and that language is pivotal to our understanding of conceptions of economics, politics, democracy and human rights in Africa. The paper, therefore, argues for the need to improve the visibility of Africa’s multilingual heritage in the teaching and research activities of African Studies institutions around the world.